First-principles investigations of the fracture toughness of NbCr2 alloyed by X (V, Mo, Ti, Fe). (1st March 2022) - Huang, Haitang; Li, Guifa; Xiao, Xuan; Lu, Shiqiang; Peng, Ping
Abstract: The room temperature brittleness of the NbCr2 Laves phase is inherent. Using first principle calculation method, the effect of alloy elements X (X = V, Mo, Ti, Fe) with 4.17 at% content on the fracture toughness of C15 NbCr2 Laves phase were characterized and evaluated by several parameters such as formation enthalpy, fracture toughness and electronic structure. The results show that although the doping of elements X (X = V, Mo, Ti, Fe) can prompt the structural stability of ternary phase NbCr2 (X), the optimized toughness of NbCr2 (X) phase is limited. The calculated fracture toughness ( K IC ) shows that the K IC of NbCr2 (X) after X (X = V, Mo, Ti, Fe) alloying is 1.55, 1.52, 1.53 and 1.49 MPa*m 1/2, respectively. Compared with 1.49 MPa*m 1/2 of NbCr2, only V, Ti and Mo have beneficial effects on the toughness of NbCr2 . Mulliken population shows that the doping of V, Mo, and Ti decreases the bonding strength of Cr–Cr covalent bonds by weakening the hybrid reaction of d -electrons. In this case, the strongly bound effect between Cr–Cr atoms is weakened, which facilitates the shear deformation and fracture toughness of NbCr2 Laves phase. Therefore, our study reveals the microscopic mechanism of V, Mo, and Ti toughening NbCr2 from the electronic structure level. Highlights: Simulations predicted fracture toughness of NbCr2 alloyed by X (V, Mo Ti and Fe). Doping of V, Mo and Ti can promote the shear deformation of NbCr2 . V, Mo and Ti reduced the Cr-Cr covalent bond by weakening the d-electron hybridization reaction. This method reveals the microscopic mechanism of alloying toughening.